The Influence of Teacher Competence in Learning and Work Motivation on Teacher Performance at SMA Negeri Sirimau District, Ambon City - Arnold Sahalessy; Vando Kristi Makaruku (Peneliti.net, 2022)
To get a quality process and student learning outcomes of course required maximum teacher performance. Teacher performance will be maximized if teachers who have in-depth mastery of the material, have good communication skills, are committed in their duties, are able to utilize learning media effectively which will help in the smooth learning process. It should be realized that the low performance of teachers can reduce the quality of education and hinder the achievement of educational goals in schools. For this reason, teacher performance needs to be managed properly so that there is no decline. This study aims to determine the significant effect of competence and work motivation on teacher performance. This research was conducted at a public high school in Sirimau District, Ambon City. In this study using a quantitative descriptive method. The research method used is the correlation, partial and simultaneous test method using the SPSS 21.0 program. The results of this study indicate, 1) there is a significant effect of competence on teacher performance with a tcount 3.287 and t-table 1.998, 2) there is a significant effect of work motivation on teacher performance with a t-count 2.663 and t-table 1.998, 3) there is an influence significant competence and work motivation on teacher performance with a value of fcount 21,258 and ftable 3,150. The conclusion is that there is a significant influence of competence and work motivation on the performance of teachers at SMA Negeri in Sirimau District, Ambon City.